2009
DOI: 10.1111/j.1468-5973.2009.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Disasters, Lessons Learned, and Fantasy Documents

Abstract: This article develops a general theory of why post-disaster 'lessons learned' documents are often 'fantasy documents'. The article describes the political and organizational barriers to effective learning from disasters, and builds on general theory building on learning from extreme events to explain this phenomenon. Fantasy documents are not generally about the 'real' causes and solutions to disasters; rather, they are generated to prove that some authoritative actor has 'done something' about a disaster. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 17 publications
6
95
0
17
Order By: Relevance
“…Driven by rapid developments after the disaster, this directive was the result of assumptions and swift decision-making concerning the distribution of tasks between the response operation and NHRP, the scope of NHRP function and responsibility, and participation in research activity into the disaster and its impacts. The directive is also important because it indexes the research pressure that Birkland and others have identified as a secondary effect of the high profile generated by major disasters (Birkland 2009, Rodriquez et al, 2007, Citraningtyas et al, 2010Brown & Donini, 2014;Gill et al, 2007). In addition to (scientific) risks to research quality, this pressure carries more immediate risks of particular concern to the response operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Driven by rapid developments after the disaster, this directive was the result of assumptions and swift decision-making concerning the distribution of tasks between the response operation and NHRP, the scope of NHRP function and responsibility, and participation in research activity into the disaster and its impacts. The directive is also important because it indexes the research pressure that Birkland and others have identified as a secondary effect of the high profile generated by major disasters (Birkland 2009, Rodriquez et al, 2007, Citraningtyas et al, 2010Brown & Donini, 2014;Gill et al, 2007). In addition to (scientific) risks to research quality, this pressure carries more immediate risks of particular concern to the response operation.…”
Section: Discussionmentioning
confidence: 99%
“…There were other instances in which local researchers, upon hearing of the NHRP, assumed this consortium was responsible for immediately acting to engage all local scientists interested in research after the disaster (many of these subsequently contributed to the research effort coordinated and funded by the NHRP). While opportunism is a factor in increased local research interest after disasters (Rodriguez et al, 2007, Birkland, 2009, the desire to contribute research skills and time to the response and to the local community is at least as significant a motivating factor. As well as marking another instance of perceived exclusion, then, the initial disappointment created by mismatched assumptions about the scope of the NHRP's role underlines the peculiar relevance research into a disaster event carries for those researchers living in the impacted region.…”
Section: Structural Boundary Decisions (And the Science/policy Interfmentioning
confidence: 99%
See 1 more Smart Citation
“…experimentation with new alternatives) may increase. Exploratory efforts in public bureaucracies have a corollary in notions of doubleloop learning (Argyris and Schön, 1996), or social policy learning (May, 1992;Birkland, 2006;2009). This type of organisational learning goes beyond adjustments in organisational programs and it is aimed at the core of the problem itself.…”
Section: Ambidextrous Learning and Adaptationmentioning
confidence: 99%
“…To please the surrounding and to a large extent politicised world, it may however suffice to pay lip service or to construct so-called fantasy documents that serve as temporary smoke-screens (cf. Birkland, 2009). It is in other words important to distinguish genuine from apparent manifestations of exploratory adaptation.…”
Section: Ambidextrous Learning and Adaptationmentioning
confidence: 99%